An empirical research on the influence of Chinese rural financial reform on cultivation of new agricultural business entities. (2nd January 2017) - Zhao, Feng; Yan, Shu-Rong; Peng, Hui; Yan, Hong-Ping; Xiao, Jian-Zhong
Abstract: The key to deepening the reform of Chinese economic system is to speed up rural financial reform, strengthen the financial support for new agricultural business entities, and accelerate cultivation and development of new agricultural business entities. The paper, taking pilot area for rural financial reform in Lishui of Zhejiang as the subject of study, makes an in-depth research on an influence of Chinese rural financial reform on cultivation of new agricultural business entities. Empirical research shows, financial support is an important means of cultivating new agricultural business entities, special finances such as governmental universal finance and special finance from financing institutions and funds in the hands of family farms exert an outstanding influence on cultivation of new rural agricultural business entities. Finance supports with different sources play a certain alternative part in cultivation of new agricultural business entities. It is very important for cultivation of new agricultural business entities to strengthen the intensity of rural financial reform and optimize allocation of rural financial resources, which indicates the direction to deepen rural financial reform of China.